2004
DOI: 10.3354/dao058035
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship among gill-infecting Myxobolus species (Myxosporea) of cyprinids: molecular evidence of importance of tissue-specificity

Abstract: The importance of tissue-specificity was studied in Myxobolus spp. infecting the gills of 7 cyprinid species. The 18S rDNA of 10 Myxobolus species was amplified by optimised nested-PCR, resulting in ~1600 bp PCR products. Phylogenetic trees generated by distance matrix and parsimony analyses revealed 4 main groups. Muscle-infecting species all belonged to the same group, while members of 2 gill-infecting groups were clearly distinguishable on the basis of tissue-specificity, and were also recognisable by diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
126
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(146 citation statements)
references
References 20 publications
17
126
0
3
Order By: Relevance
“…n. clustered with M. feisti, M. margitae, and M. macrocapsularis and formed an independent clade among cyprinid fish-infecting Myxobolus species but genetically distant from M. basilamellaris. Previous reports showed that genetic separation is a more ancient evolutionary feature than host specificity based on the tissue tropism (Eszterbauer 2004). However, M. feisti develop in a cartilaginous gill ray of the roach surrounding by chondrocytes, M. margitae inside the afferent arteries of the gill filaments of bleak, Alburnus alburnus, and M. macrocapsularis in the filament artery of apical part of the gill filaments of white bream (Molnár 2000;Molnár et al 2008Molnár et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…n. clustered with M. feisti, M. margitae, and M. macrocapsularis and formed an independent clade among cyprinid fish-infecting Myxobolus species but genetically distant from M. basilamellaris. Previous reports showed that genetic separation is a more ancient evolutionary feature than host specificity based on the tissue tropism (Eszterbauer 2004). However, M. feisti develop in a cartilaginous gill ray of the roach surrounding by chondrocytes, M. margitae inside the afferent arteries of the gill filaments of bleak, Alburnus alburnus, and M. macrocapsularis in the filament artery of apical part of the gill filaments of white bream (Molnár 2000;Molnár et al 2008Molnár et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Most of Myxobolus species of cyprinid fishes select a specific site for their sporulation, and tissue tropism was thought to be one of important taxonomic features (Eszterbauer 2004;Molnár et al 2014). Up to now, more than 260 Myxobolus species have been reported to infect the fish gills (Eiras et al 2005(Eiras et al , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, this method always failed to identify the highly similar species that are found in the same tissue and host, which only have subtle differences in spore size and shape. Fortunately, this problem was solved through the molecular approach (Smothers et al 1994;Kent et al 1998;Andree et al 1999;Astrid et al 2004;Eszterbauer 2004). Nowadays, morphologic description of myxozoan species is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…n. (Ali et al 2002); most of these species were reported to infect gills of the host. Exact infection location and tissue tropism are important characters for specific assignment (Molnár 1994;Eszterbauer 2004). M. follius, M. lokiaensis and M. fahmii were noticed to have similar spore shape with M. pyramidis.…”
Section: Discussionmentioning
confidence: 99%